PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI FINISHING PT. PAPYRUS SAKTI PAPER MILL - Septiani, Ajeng; Siddiq, Andhika Mochamad; Saputro, Arie Hendra (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
The objective of this analysis is to evaluate the impact of factors such as motivation, work environment, and job satisfaction on the overall performance of employees in the finishing department at PT. Papyrus Sakti Paper Mill. Employee performance plays a critical role in the achievement of the company's goals, making it essential to identify the factors influencing this aspect. The research adopted a quantitative approach, utilizing questionnaires administered to the personnel within the finishing department. Multiple linear regression analysis was employed to determine the significance of each independent variable namely work motivation, work environment, and job satisfaction on the dependent variable, which is employee performance. The results reveal that all three factors work motivation, work environment, and job satisfaction exhibit a positive and statistically significant influence on employee performance, both individually and in combination. The work environment exerts the most significant influence on employee performance, followed by job satisfaction, with work motivation having a lesser but still considerable impact.